Structure and electrochromism of two-dimensional octahedral molecular sieve h’-WO3 - Besnardiere, Julie; Ma, Binghua; Torres-Pardo, Almudena; Wallez, Gilles; Kabbour, Houria; González-Calbet, José M.; Von Bardeleben, Hans Jürgen; Fleury, Benoit; Buissette, Valérie; Sanchez, Clément; Le Mercier, Thierry; Cassaignon, Sophie; et al. (Nature communications, 2019)
Octahedral molecular sieves (OMS) are built of transition metal-oxygen octahedra that delimit sub-nanoscale cavities. Compared to other microporous solids, OMS exhibit larger versatility in properties, provided by various redox states and magnetic behaviors of transition metals. Hence, OMS offer opportunities in electrochemical energy harnessing devices, including batteries, electrochemical capacitors and electrochromic systems, provided two conditions are met: fast exchange of ions in the micropores and stability upon exchange. Here we unveil a novel OMS hexagonal polymorph of tungsten oxide called h’-WO 3 , built of (WO 6 ) 6 tunnel cavities. h’-WO 3 is prepared by a one-step soft chemistry aqueous route leading to the hydrogen bronze h’-H 0.07 WO 3 . Gentle heating results in h’-WO 3 with framework retention. The material exhibits an unusual combination of 1-dimensional crystal structure and 2-dimensional nanostructure that enhances and fastens proton (de)insertion for stable electrochromic devices. This discovery paves the way to a new family of mixed valence functional materials with tunable behaviors. Thanks to their versatile redox behaviors, octahedral molecular sieves show promise in a range of electrochemical applications. Here the authors report a hexagonal polymorph of tungsten trioxide, an octahedral molecular sieve that exhibits fast proton (de)insertion for electrochromic devices.